Ion irradiation effects on FeCrAl-ODS ferritic steel. (May 2018) - Kondo, K.; Aoki, S.; Yamashita, S.; Ukai, S.; Sakamoto, K.; Hirai, M.; Kimura, A.
Highlights: Fe ion irradiation effect on 12Cr-6Al ODS ferritic steel was studied. Radiation hardening in 12Cr-6Al ODS ferritic steel was mainly caused by the irradiation defect clusters up to the irradiation dose of 5 dpa. It was considered that the effect of formation of α' phase on the hardening might appear with increasing the irradiation dose toward 20 dpa. Abstract: The correlation between microstructure and mechanical property of ion irradiated 12Cr-6Al ODS ferritic steel was studied. Ion irradiation experiments were performed using 10.5 MeV Fe ions up to the nominal displacement damage of 20 dpa with the damage rate of 1 × 10 − 4  dpa/s, while the irradiation temperature was 300 °C. Oxide nanoparticles showed stable size distribution and mean size under ion irradiation up to 20 dpa. The irradiation microstructure examined by TEM revealed that the mean size and number densities of irradiation-induced defect clusters increased with the displacement damage. The correlation between irradiation microstructure and radiation hardening was theoretically calculated using the dispersed barrier hardening model. The results showed a good agreement with the experimentally measured hardness data up to irradiation at 5 dpa, while a slight discrepancy was found between theoretical and experimental hardness values under irradiation at 20 dpa. Radiation hardening in 12Cr-6Al ODS ferritic steel was mainly caused by irradiation-induced defect clusters below the irradiation dose of 5 dpa. As the irradiation dose increased toward 20 dpa, an additional influence of the radiation appeared, which was assumed to be induced by α' phase transformation.